Additive Manufacturing As An Application Of Information Technology As A Method Of Product Development In The Automotive Industry - Wibowo Harry Sugiharto; Muhammad Imam Ghozali (Institute of Computer Science (IOCS), 2022)
Additive manufacturing, or 3D printing, is revolutionizing manufacturing; it is a process for creating 3D objects in any form from 3D modeling simulations. 3D printed models can be created with a computer-aided design (CAD) package, via a 3D scanner, or with an ordinary digital camera and photogrammetry software. Additive manufacturing has been used in manufacturing, culinary industry, medical applications, healthcare, fashion industry, education, and the automotive industry. The Automotive Industry has contributed significantly to the national economy of Indonesia. The Automotive Industry is currently one of seven sectors prioritized in developing Industry 4.0 in accordance with the Making Indonesia 4.0 roadmap. The product development process using the additive manufacturing method is broadly divided into three stages: modeling, printing, and finishing. An example of the application of additive manufacturing technology in product development at the Automotive MSME level in the manufacture of velocity stack products. The working principle of this tool is to reduce intake air losses (intake air coefficient effect). The results of the velocity design test on the Yamaha MX King can increase engine power average in 1.45 HP and average torque 1.19 NM